Environmental management for hotels : a student's handbook - Kirk, D. (David), 1945- (Oxford ; Boston : Butterworth-Heinemann, 1996)
Environmental management for hotels; Environmental system-policy, strategy, & implementation; Assessment; Management of water, energy, waste, indoor environment.
Keywords: Hotels; Hotel management; Hotel management -- Handbooks, manuals, etc; Hotels -- Environmental aspects -- Handbooks, manuals, etc; Environmental aspects -- Handbooks, manuals, etc